Psychological effects and associated factors among vaccinated and unvaccinated general population against COVID-19 infection in Bangladesh - Alam, Md. Dhedharul; Abedin, Md. Joynal; Islam, Asraful; Mosfeq-Ul-Hasan, Md.; Rahman, Obaydur; Xu, Yi (Frontiers in Psychiatry, 2022)
Background The global effort to develop herd immunity in the general public against the COVID-19 pandemic is currently ongoing. However, to the best of our knowledge, there have been no studies on how the COVID-19 vaccine affects mental health in the context of the COVID-19 pandemic in Bangladesh. The present study investigated the psychological effects and associated factors among vaccinated and unvaccinated general populations against COVID-19 infection in Bangladesh. Methods A nationwide online cross-sectional survey was conducted in Bangladesh from June 23 to December 25, 2021. The frequency of symptoms of psychological distress, depression, anxiety, stress, post-traumatic stress disorder (PTSD), insomnia, and fear was assessed using the Bangla versions of the GHQ-12, PHQ-2, GAD-2, PSS-4, PC-PTSD-5, ISI, and FCV-19S scales, respectively. Results The study included 3,013 persons from all eight divisions of Bangladesh, with 1,272 (42.2%) being vaccinated and 1,741 (57.8%) being unvaccinated. Compared with unvaccinated populations, vaccinated populations had significantly lower prevalence rates of psychological distress (36.4 vs. 51.5%), depression (21.1 vs. 37.9%), anxiety (25.1 vs. 44.9%), stress (19.4 vs. 30.4%), PTSD (29.4 vs. 38.3%), insomnia (18.7 vs. 39.4%), and fear symptoms (16.1 vs. 27.5%). Among vaccinated populations, respondents who lived in nuclear families were significantly associated with higher risk of psychological distress (AOR, 1.38; 95% CI, 1.09–1.78), depression (AOR, 1.49; 95% CI, 1.11–1.98), anxiety (AOR, 1.77; 95% CI, 1.21–1.98), and fear (AOR, 1.43; 95% CI, 1.11–1.83) symptoms. Participants who lost family members, friends, or colleagues due to the COVID-19 pandemic had significantly higher risk of symptoms of psychological distress (AOR, 1.35; 95% CI, 1.02–1.79), anxiety (AOR, 1.41; 95% CI, 1.11–1.87), and PTSD (AOR, 1.76; 95% CI, 1.24–2.19). On the other hand, unvaccinated populations who lived in the Dhaka division were significantly associated with an increased risk of depression (AOR, 2.06; 95% CI, 1.40–2.52), anxiety (AOR, 1.86; 95% CI, 1.15–2.47), stress (AOR, 1.92; 95% CI, 1.12–2.88), and insomnia (AOR, 1.88; 95% CI, 1.20–2.94) symptoms. Except for PTSD and fear symptoms, unemployed participants had considerably higher rates of psychological distress, depression, anxiety, stress, and insomnia symptoms (e.g., psychological distress: AOR, 1.83; 95% CI, 1.10–2.62; depression: AOR, 1.74; 95% CI, 1.37–2.19). Conclusions This study recommends immunizing unvaccinated populations as soon as possible to prevent infection and boost mental health. Vulnerable people needed special care, health-related education, and psychological assistance.